THE EUROPEAN UNION: ITS INTERNATIONAL IDENTITY AND THE VALUES AT ITS CORE - Moskalenko, Oleksandr M. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: The article studies the issue of the EU international identity as well as the values this identity is constructed on. The article emphasizes the importance of this identity both from theoretical and from practical perspectives, and claims that the liberal democracy governance model makes up the foundation of the EU identity. Methods: theoretical and methodological basis of this article is made up by the concepts of social constructivism, European constitutionalism and new institutionalism. Discussion: provides new perspective regarding the essence of the EU international identity, its importance for the EU performance at the international arena as well as the role that institutions are considered to play for identity formation. Moreover, the article offers the analysis of Normative Power Europe as the major explanatory concept for EU relations with third countries and studies the values that the EU identity is constructed on.